AUTOMATION OF BELT GRINDER FOR ABRASIVE PROCESSING OF PARTS - Raubiška, Daniels; Koļčs, Guntis (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2023)
This publication shows the lifting mechanism for the abrasive processing of belt grinding machine parts and its control automation. The Nextion display and Arduino Nano were used for this project. They will be used to control the lifting mechanism of the equipment and the frequency converter.